A Comparison of the Effectiveness of Varenicline and Transdermal Nicotine Patch in Outpatients Following a Standardized Smoking Cessation Program in Southern Taiwan. (March 2015) - Hsueh, Shu-Chun; Hsueh, Kuang-Chieh; Chou, Ming-Yueh; Tu, Ming-Shium
`Varenicline use has been shown to produce greater long-term smoking cessation rates than bupropion but has no clear differences compared to the transdermal nicotine patch. We performed this study to compare the effectiveness of varenicline with the nicotine patch at 3 and 6 months of follow-up of patients in an outpatient smoking cessation program provided by a hospital in Southern Taiwan. The sample consisted of 463 patients who attended the smoking cessation program at the outpatient family medicine clinic at Kaohsiung Veterans General Hospital between March 2006 and December 2008. All patients were aged ≥18 years and either smoked ≥10 cigarettes per day or scored ≥4 on the Fagerström Test for Nicotine Dependence. Patients were seen by a physician for up to 8 sessions in 90 days. Medication use was guided by patient preference (208 opted for varenicline and 255 for the nicotine patch). The primary outcomes of the study were self-reported 7-day point prevalence abstinence rates at 3 and 6 months from the first clinic visit. Varenicline users had a significantly higher abstinence rate than those using nicotine patch at 3-month (47.1% vs. 30.6%; odds ratio [OR] = 2.02, 95% confidence interval [CI] = [1.38, 2.96]) and 6-month follow-up (41.3% vs. 30.6%; OR = 1.60, 95% CI [1.09, 2.32]). Both groups had similar incidences of adverse events. Varenicline use in a sample of treatment-seeking-dependent smokers was associated with significantly higher abstinence rates than the nicotine patch.